100% PVDF 3D textiles structures to improve energy harvesting. Issue 1 (April 2020) - Talbourdet, A; Cochrane, C; Rault, F; Lemort, G; Campagne, C; Devaux, E
Abstract: With a final view to prototyping a textile energy harvesting system, piezoelectric textile structures based on 100% poly(vinylidene fluoride) (PVDF) were developed and characterized. Multifilaments of 246 tex were produced by melt spinning. The mechanical stretching during the process provides PVDF fibers with an optimal β-phase ratio (97%). Some studies have already been carried out on piezoelectric PVDF-based structures as films or textiles. The goal of the study is the investigation of the differences between 2D and 3D woven fabrics structures from piezoelectric PVDF multifilament yarns. The textile structures were poled after the weaving process, and a maximum output voltage of 2.3 V was observed on an angle - through-the-thickness interlock (interlock 3D structure) under compression by DMA tests. Energy harvesting is optimized in a 3D interlock thanks to the stresses of the multifilaments in the thickness. This finding has led to the design of an inner sole prototype from a knitting structure and another structure with piezoelectric fibers outside the plane of the fabric. The prototype is able to harvest energy and the results are consistent with the measurement realized with DMA under dynamic compression close to walking.